Large-Scale Molecular Dynamics Simulations of Cellular Compartments - Wilson, Eric; Vant, John; Layton, Jacob; Boyd, Ryan; Lee, Hyungro; Turilli, Matteo; Hernández, Benjamín; Wilkinson, Sean; Jha, Shantenu; Gupta, Chitrak; Sarkar, Daipayan; Singharoy, Abhishek (Springer Nature, 2021)
Molecular dynamics or MD simulation is gradually maturing into a tool for constructing in vivo models of living cells in atomistic details. The feasibility of such models is bolstered by integrating the simulations with data from microscopic, tomographic and spectroscopic experiments on exascale supercomputers, facilitated by the use of deep learning technologies. Over time, MD simulation has evolved from tens of thousands of atoms to over 100 million atoms comprising an entire cell organelle, a photosynthetic chromatophore vesicle from a purple bacterium. In this chapter, we present a step-by-step outline for preparing, executing and analyzing such large-scale MD simulations of biological systems that are essential to life processes. All scripts are provided via GitHub
Keywords: 33 Ciencias Tecnológicas::3306 Ingeniería y tecnología eléctricas; ODS 3 - Salud y bienestar; Multiscale simulation; Molecular dynamics; Photosynthetic chromatophore; NAMD; VMD; Ensemble toolkit; High-performance computing